Preoperative peripheral and core temperature: an observational study at a day-surgery unit. (13th February 2020) - Matilda, Ek; Westergaard-Nielsen, Emma; Henricson, Maria
Abstract : Background: Hypothermia is a common problem in the surgical context and can lead to serious consequences for the patient and increased costs for society. Aims: To study day-surgery patients' peripheral and core temperatures during the preoperative phase. Methods: In total, 50 day-surgery patients participated in the study. Two sets of measurements of temperatures were made: core temperature and peripheral temperatures (two measuring points on the upper body and lower extremities respectively) were measured on arrival at the day-surgery unit, as well as on arrival at the operating theatre. The data were normally distributed and a paired t-test was used for statistical analysis. Findings: Peripheral temperatures had significant changes, with measuring points on the upper body decreasing and measuring points on the lower extremities increasing in temperature. The results show no significant change in core temperature. Conclusion: The measurements show that 28% of the patients were below recommended preoperative temperature on arrival at the operating theatre. Further research is needed to study the development of body temperature perioperatively as well as at what point reheating interventions should be introduced.